Pemanfaatan Limbah Serat dari Pelepah Pisang sebagai Inovasi Bahan Komposit Laminasi Kapal Kayu - Mu'aazar Habibie, Ahmad; Basuki widodo, Akhmad (Fakultas Teknik, Universitas Bhayangkara Jakarta Raya, 2022)
Fishing boats are vessels that almost 90% ofthe building materials are made of wood. Thenature of wood that is easily weathered andattacked by wood destroying organisms causesfishing vessels with wood materials to be easilydamaged. Banana trees are plants that thrivein Indonesia. In addition to the fruit, bananatree leaves are the part that is often used forreprocessing. However, the midrib of the treecannot be utilized optimally and will becomeunused waste. Therefore, the author has aninnovation using banana midrib fiber as acomposite material as a wood ship laminationmaterial. Therefore, researchers need to do atest, namely by tensile test of variations in fiberthickness of 1 layer, 2 layers, 3 layers on abanana midrib fiber composite and polyesterresin to measure the tensile strength value ofthe composite which refers to the ASTM 63802astandard.